Spain and the Catholic Church. Report of interview, 31.10.36 : inter-departmental correspondence - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
019-0018-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From DR. H.B. MORGAN. To MISS F. McDONALD. Department Social Insurance. Date 5th November, 1936. SUBJECT. SPAIN AND THE CATHOLIC CHURCH. Report of Interview, 31.10.36. I have made no comments of a personal character, because I do not know whether Sir Walter wanted me to make them, but if he prefers me to do so, I will let him have them in addition to this Report, which he may take as authentic. 292/946/19/18